Risk Management Practices Among Accommodation Facilities in Ormoc City - Polinar, Mark Anthony N.; Dadulla, Daffodel M.; Payao, Ronald B. (Future Science / FSH-PH Publications, 2023)
This study aims to ascertain the degree of impact and likelihood of the various risks, as well as the risk management method implementation among lodging facilities. In addition, the study took into account the link between the likelihood and impact of the various risks. To achieve this goal, a quantitative method engaging in a descriptive approach was with 128 respondents from 30 establishments who got involved in the study from the top management to rank and file through a self-completed survey. The level of the risk management process among the establishments showed a